Insects induced mango fruit rot: unraveling the culprits - Subramaniam, Sivagami; Md Noordin, Noor Aisyah; Wahid, Noor Azrizal; Mohd Zainudin, Nur Ain Izzati (Universitas Andalas, 2024)
nt diseases and pests are important factors determining plant yield production, including mango. Mango is an economically important fruit crop in tropical and subtropical areas.Mango fruit rot caused by insects and microbes has become a significant threat to mango production in Southeast Asia and worldwide. Insect plant pathogens affect crop yields' profitability, quality, and quantity. Some infections could occur before harvest and remain dormant until the favourable condition is achieved, and the disease will break out after harvest, reducing mango production. They act as a threat to the crops through various mechanisms of pathogenesis that compromise the immune system of the plants, such as developing any ways to attack theplants, seeking entry viaopen pores or exposed surface or wound, and sourcing nutrients forcefully for their growth and development. Depending on the environmental factors, the insect contracts the host through primary or secondary infection. This paper summarizes mango fruit rotdisease caused by insects groups such as fruit borers (Autocharis albizonalisand Citripestis eutraphera), fruit flies (Bactrocera dorsalis), and mango seed weevils (Sternochetus mangiferae). This review will provide information about fruit rot diseases on mangoes caused by insects, the mechanism of infection, the interaction between insect damage and fungal infections, effective control methods, and related integrated pest management approaches